Workshop AI Untuk Pengembangan Media Pembelajaran Interaktif Pada MGMP Guru SMK TSM di Kabupaten Pekalongan - Fenilinas Adi Artanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The industrial revolution 4.0 has brought about major transformations in various aspects of life, including the world of education, especially through the application of Artificial Intelligence (AI) technology in the teaching and learning process. However, most teachers in Indonesia still have limitations in understanding and are also still lacking in skills in utilizing this technology. This community service activity aims to improve the competence of teachers, especially teachers at the Motorcycle Engineering Vocational School (TSM) Expertise Program Teacher Conference (MGMP) in Pekalongan Regency in developing learning media based on Artificial Intelligence (AI). The implementation was carried out through a two-session workshop that combined theory and practice, and assistance in utilizing Artificial Intelligence (AI) technology. Several applications such as ChatGPT, Copilot and also Meta AI and other platforms were used. Evaluation was carried out through observation, questionnaires and analysis of participants' work. The results of the activity showed an increase in teachers' understanding and skills in using Artificial Intelligence (AI) as a learning medium. This activity is expected to be the first step in building a technology-based innovation culture in the education environment.